Comparative Analysis of Naïve Bayes and SVM Algorithms for Early Detection of Lung Disease at Cimuning Community Health Center - Jordi Hafidz; Aji Setiawan (Journal TIFDA (Technology Information and Data Analytic), 2025)
Comparative Analysis of Naïve Bayes and SVM Algorithms for Early Detection of Lung Disease at Cimuning Community Health Center